IMPROVING DEPRECIABLE FIXED ASSET ACCOUNTING. - Bornemann, Alfred (The Accounting Review, 1953)
Fixed asset accounting is of fundamental importance in public utilities and railroads because of the relationship between the valuation of property and the rates in those industries. While there is no precise uniformity in the regulations of the various jurisdictions, the general rule is to provide definitions of property units suitable for the particular industry. These units are fairly carefully defined in the uniform systems of accounts and accountants can refer to the manuals at any time that a fixed asset work order requires a distribution. In as much as differences of opinion regarding the interpretation of some transactions are sometimes possible, it would be an exaggeration to claim that the procedures result in complete accuracy in an abstract sense. However, there is no doubt that written definitions of fixed asset units help to promote uniformity. As a general rule, definitions of public utility and railroad units of property were originally determined by engineers. Once they had been satisfactorily defined, however, accountants experienced no particular difficulty in using them for accounting purposes.